Character Formation Based on North Sumatra Local Wisdom Through Orchestral Learning in Music Education Study Program, Universitas Negeri Medan - Adina Sembiring; Uyuni Widiastuti; Octaviana Tobing; Esra Siburian; Hendy Obed Sembiring; Ewin Johan Sembiring (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The objectives of this study are to: (1) Producing character building based on North Sumatra local wisdom through orchestral learning in Music Education Study Program,  Unimed; (2) Producing orchestral learning that can shape the character of students in the Music Education Study Program; (3) Producing characters that are formed through orchestral learning in Music Education Study Program,  Unimed. It is expected that the existence of research on the topic of orchestral learning in Music Education Study Program,  Unimed  can shape character based on local wisdom in North Sumatra